Association between brain activation (fMRI), cognition and school performance in extremely preterm and term born children. Issue 5 (9th July 2014) - Griffiths, Silja Torvik; Aukland, Stein Magnus; Markestad, Trond; Eide, Geir Egil; Elgen, Irene; Craven, Alexander R; Hugdahl, Kenneth
<x xml:space="preserve">Abstract</x> The purpose of the study was to investigate a possible association between brain activation in functional magnetic resonance imaging scans, cognition and school performance in extremely preterm children and term born controls. Twenty eight preterm and 28 term born children were scanned while performing a working memory/selective attention task, and school results from national standardized tests were collected. Brain activation maps reflected difference in cognitive skills but not in school performance. Differences in brain activation were found between children born preterm and at term, and between high and low performers in cognitive tests. However, the differences were located in different brain areas. The implication may be that lack of cognitive skills does not alone explain low performance due to prematurity.